Personalized Antiplatelet Therapy Based on CYP2C19 Genotypes in Chinese ACS Patients Undergoing PCI: A Randomized Controlled Trial - Shi, Xiujin; Zhang, Yunnan; Zhang, Yi; Zhang, Ru; Lin, Baidi; Han, Jialun; Li, Wenzheng; Fang, Zhenwei; Yan, Jialin; Wang, Yifan; Zheng, Ze; Lv, Yuan; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The clinical benefits of cytochrome P450 (CYP) 2C19 genotype-guided antiplatelet therapy in Asians remain unclear. In this study, we aimed to investigate the clinical outcomes of pharmacogenomic antiplatelet therapy in Chinese patients. Methods: Patients with acute coronary syndrome planning to undergo percutaneous coronary intervention were eligible for this study and were randomly divided into a genotype-guided treatment (GT) group and routine treatment (RT) group, with a ratio of 2:1. Patients in the GT group underwent CYP2C19 genotyping (*2 and *3 alleles), and the results were considered in selecting P2Y12 receptor inhibitors. Patients in the RT group were treated with P2Y12 receptor inhibitors according to their clinical characteristics. The primary endpoint was a composite of major adverse cardiovascular or cerebrovascular events (MACCE). The secondary endpoint was significant bleeding events. Results: Finally, 301 patients were enrolled; 75.1% were men and the mean age was 59.7 ± 9.8 years. In total, 281 patients completed the follow-up procedure. The primary endpoint occurred in 16 patients, 6 patients in the GT group and 10 in the RT group. The GT group showed lower MACCE rates than the RT group (6/189 vs. 10/92, 3.2 vs. 10.9%, hazard ratio: 0.281, 95% confidence interval: 0.102–0.773, P = 0.009). There was no statistically difference in significant bleeding events between the GT and RT groups (4.2 vs. 3.3%, hazard ratio: 1.315, 95% confidence interval: 0.349–4.956, P = 0.685). Conclusion: Personalized antiplatelet therapy that is based on CYP2C19 genotypes could decrease MACCE within a 12-month period in Chinese patients with acute coronary syndrome undergoing percutaneous coronary intervention. Clinical Trial Registration:http://www.chictr.org.cn, identifier: ChiCTR2000034352.